2003
DOI: 10.1007/s00059-003-2524-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACE Inhibition versus Non-ACE Inhibitor Antihypertensive Treatment on Myocardial Fibrosis in Patients with Arterial Hypertension

Abstract: In patients with hypertensive heart disease, myocyte hypertrophy and myocardial fibrosis are present. Myocardial fibrosis and not myocyte hypertrophy determines myocardial stiffness. ACEI appear to diminish myocardial fibrosis associated with enhanced collagen degradation irrespective of LVH regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
1
29
0
4
Order By: Relevance
“…88,89 Alternatively, kidney function is also responsible for age-associated mouse 90 and rat deaths, 91 and lower blood pressure associated with inhibiting the RAS may also reduce kidney damage. Recent data suggest that cardiac function, which is also adversely affected by angiotensin signaling, 73 may be partially responsible for mouse deaths. 89,92 AT1 angiotensin receptor inhibitors have been reported to inhibit the formation of circulating MDA-modified LDLs in human diabetic patients and the modification by MDA of lungs in rats affected with bleomycin-induced pulmonary fibrosis.…”
Section: Example #1: Renin-angiotensin Systemmentioning
confidence: 99%
“…88,89 Alternatively, kidney function is also responsible for age-associated mouse 90 and rat deaths, 91 and lower blood pressure associated with inhibiting the RAS may also reduce kidney damage. Recent data suggest that cardiac function, which is also adversely affected by angiotensin signaling, 73 may be partially responsible for mouse deaths. 89,92 AT1 angiotensin receptor inhibitors have been reported to inhibit the formation of circulating MDA-modified LDLs in human diabetic patients and the modification by MDA of lungs in rats affected with bleomycin-induced pulmonary fibrosis.…”
Section: Example #1: Renin-angiotensin Systemmentioning
confidence: 99%
“…1 Furthermore, a recent systematic review shows that HF development remains a major problem in treated hypertensive patients. 2 It has been shown that myocardial fibrosis, a common finding in postmortem studies and endomyocardial biopsies of patients with hypertensive heart disease (HHD), 3 is associated with the increase of left ventricular (LV) chamber stiffness 4,5 and the development of clinically overt HF in these patients. 6,7 It has been proposed that the increase in LV stiffness can contribute to compromised diastolic function and elevate left-sided filling pressures (FPs) in hypertensive patients.…”
mentioning
confidence: 99%
“…Obgleich ACE-Hemmer im Tierexperiment in der Therapie die kardiale Fibrose völlig reversibel gestalten, können sie diese beim Menschen nur vermindern. Wie am Beispiel der arteriellen Hypertonie bioptisch gezeigt werden konnte, ist diese reverse Remodeling auch bei adäquater antihypertensiver Therapie nicht vollständig (Abbildung 13) [5]: In linksventrikulären Myokardbiopsien konnte die Kollagenvolumenfraktion zwar von 7,6% auf 5,3% vermindert werden, lag aber trotzdem noch immer erheblich über den Kontrollen mit 0,5%. Die myokardiale Steifigkeit ist zusätzlich infolge einer inadäquaten SERCA-2-Expression gesteigert, die zur gestörten Relaxation entscheidend beiträgt (Abbildung 11).…”
Section: Pathomechanismenunclassified
“…Im Hochdruckherzen ist der Vorgang komplexer. Dort sind in den Biopsien das inaktive Pro-MMP-2 vermindert und Pro-MMP-9 gesteigert [5] (Abbildung 28).…”
Section: Kollagenabbau Und Ventrikeldilatationunclassified